Forty Years of Price Transmission Research in the Food Industry: Insights, Challenges and Prospects. (28th December 2016) - Lloyd, Tim
Abstract: Price transmission refers to a process via which information is transmitted between participants in a market. Focusing on vertical markets such as the food chain, this Address considers developments in theory, methods and data that help economists understand how information is conveyed between food consumers and agricultural producers. Central to this understanding is the increasingly important role played by the food industry (retailing, manufacturing and processing) in price transmission. Not only is the food industry a major source of the price changes that producers and consumers face but it also mediates price signals originating in other parts of the food chain in increasingly nuanced ways, as revealed by highly detailed retail ('scanner') data that is becoming progressively available to researchers. While the speed, magnitude and asymmetry of price transmission are valuable descriptors of price adjustment in vertical markets, we should be wary of inferring too much about the competitive setting on the basis of prices alone. Theory‐consistent empirical models are a step in the right direction and represent a useful complement to the approaches developed in the New Empirical Industrial Organisation literature which address the issue of market power directly. Being the mechanism underlying food inflation, price transmission also has an important macro‐economic dimension, and concerns about competition surface here too. Given the rapidly changing nature of the food industry in many countries, the need to understand the forces shaping price transmission is as cogent as ever.